2013
DOI: 10.3329/bjas.v42i1.15777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methionine supplementation on the growth performance of rabbit

Abstract: The present study was conducted to evaluate the effect of different levels of methionine supplementation on feed intake, nutrient digestibility and growth performance of growing rabbit. Sixteen weaned crossbred New Zealand White (NZW) growing rabbits (30-35 d) were distributed into four treatment groups having four replications in each group using a Completely Randomized Design (CRD). Basal diet composed of green grass (dhal grass) and concentrate mixture which was offered ad libitum basis for 56 days period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…These results agree with others previously obtained, where lysine, methionine or threonine supplementation did not affect the digestibility of DM, CP, and GE [ 32 , 33 , 34 ]. However, recent studies have observed that dietary supplementation with methionine from 2.4 to 4.9 g/kg [ 35 ] or from 5.6 to 8.3 g/kg [ 36 ] could increase the CTTAD of DM, CP and GE in growing rabbits. In any case, ref.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with others previously obtained, where lysine, methionine or threonine supplementation did not affect the digestibility of DM, CP, and GE [ 32 , 33 , 34 ]. However, recent studies have observed that dietary supplementation with methionine from 2.4 to 4.9 g/kg [ 35 ] or from 5.6 to 8.3 g/kg [ 36 ] could increase the CTTAD of DM, CP and GE in growing rabbits. In any case, ref.…”
Section: Discussionmentioning
confidence: 99%
“…Met supplementation significantly increased the digestibility of dry matter and crude protein in rabbits. The dietary addition of 0.35% methionine significantly increased the protein digestibility of growing rabbits [ 28 ]. The addition of Met in diet has a favorable effect on nitrogen balance, nitrogen retention coefficient, growth performances and feed efficiency of rabbits [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of Ca-Aminoplex on body weight gain of growing rabbits could be attributed to its content of essential amino acids, vitamin B complex and calcium. Growth rate of rabbits was markedly enhanced by addition of vitamin B6 (Gihan, 2017), lysine (Taboada, et al, 1994 andJing andLifu, 2010), methionine (Al-Homidan, 2001;Zhang andLi, 2010 andYesmin, et al, 2013). Also, Osman et al, (2007) indicated that, broiler chicks must be injected at least two times with Ca-Aminoplex to maximize its profitability.…”
Section: Effect Of Ca-aminoplexmentioning
confidence: 99%